1978
DOI: 10.1111/j.1348-0421.1978.tb00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological Studies on the Major Histocompatibility Complex of New Inbred Strains of the Guinea Pig1

Abstract: New inbred strains of guinea pigs, JY 1, JY 2, JY 3, JY 6, JY 9 and JY 10 have been established in this Institute. Serologic studies of guinea pig leukocyte antigens (GPLA antigens) were carried out in order to examine their major histocompatibility complex (GPLA complex). Antisera specific for Ia antigens were raised by cross-immunization of NIH strain 2 (NIH 2) and NIH strain 13 (NIH 13) guinea pigs, well known inbred guinea pigs. The sera identified four distinct Ia specificities, which were designated as I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
15
1

Year Published

1978
1978
1995
1995

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 9 publications
1
15
1
Order By: Relevance
“…The PLL gene, which has been demonstrated to link to MHC of NIH 2 guinea pigs, was found in none of the inbred strains. As one of the Ia specificity of NIH 2 guinea pigs, which was designated as Ia.2b (Chiba et al, 1978) was detected in JY 2 guinea pigs, the presence of the PLL gene in JY 2 guinea pigs was expected but it was not found. This result indicates no association between the PLL gene and Ia.2b detected in JY 2 guinea pigs.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The PLL gene, which has been demonstrated to link to MHC of NIH 2 guinea pigs, was found in none of the inbred strains. As one of the Ia specificity of NIH 2 guinea pigs, which was designated as Ia.2b (Chiba et al, 1978) was detected in JY 2 guinea pigs, the presence of the PLL gene in JY 2 guinea pigs was expected but it was not found. This result indicates no association between the PLL gene and Ia.2b detected in JY 2 guinea pigs.…”
mentioning
confidence: 99%
“…Since an association between the PLL gene and Ia.2 was recently demonstrated (Shevach et al, 1977), Ia.2b may be distinct from Ia.2. The other Ia specificity, which was recognized by NIH 13 anti-NIH 2 serum and designated as Ia.2a (Chiba et al, 1978), is expected to be Ia.2, since Ia.2a was detected in NIH 2 guinea pigs but not in inbred strains of guinea pigs established in this Institute (Chiba et al, 1978) and the PLL gene being detected in NIH 2 guinea pigs was found in none of the inbred strains as described above.…”
mentioning
confidence: 99%
See 3 more Smart Citations